Prognostic role of mid-regional pro-adrenomedullin in predicting infection in pediatric cancer with febrile neutropenia - Seham M. Ragab; Sara Mahmoud El-Deeb; Ahmed Saeed; Asmaa A. Mahmoud (Clinical and Experimental Pediatrics)
Background Febrile neutropenia (FN) remains an important complication of cytotoxic chemotherapy for which an urgent and appropriate evaluation is imperative. Purpose To assess the diagnostic and prognostic roles of mid-regional pro-adrenomedullin (MR-ProADM) levels in predicting infection in patients with FN. Methods This comparative cross-sectional study included 137 patients with chemotherapy-induced FN. Complete blood count, C-reactive protein (CRP), procalcitonin (PCT), and MR-ProADM were evaluated on the 1st day of FN. Chest computed tomography was performed on the 5th day. Results MR-ProADM levels were significantly higher in patients with FN than in controls. CRP and MR-ProADM levels were significantly higher and absolute neutrophil count (ANC) was significantly lower in patients with versus without bacterial infections. CRP, PCT, and MR-ProADM levels were significantly negatively correlated with ANC. CRP, PCT, and MR-ProADM levels were significantly and positively correlated with FN degree, FN duration, and hospital stay length. A multivariate regression analysis showed that a longer FN duration and hospital stay length, along with elevated CRP, PCT, and MR-ProADM levels, were significant risk factors for mortality. Conclusion MR-ProADM is a reliable prognostic and diagnostic tool for predicting infection in patients with FN.